A comprehensive review and meta-analysis of the relationships between interleukin-7 levels and COVID-19 severity - Michal MATUSZEWSKI; Michal PRUC; Lukasz SZARPAK; Alla NAVOLOKINA; Katarzyna KIEZUN; Francesco CHIRICO; Gabriella NUCERA; Yuriy STEPANOVSKYY; Murat YILDIRIM; Anna HILFANOVA; Anastasia BONDARENKO (Journal of Health and Social Sciences, 2023)
Introduction: As the major mechanism for coronavirus disease 2019, cytokine storm-mediated organ harm continues to dominate current understanding. Despite the first hyper-inflammatory phase, emerging data show that virus-induced poor host immunity may be the true cause of mortality in many individuals. Interleukin 7 (IL-7) is an interleukin that participates in the COVID-19 cytokine storm and regulates the immune system. Its role in COVID-19 cytokine storms is thought to be related to its ability to stimulate the formation and activation of immune cells such as T cells and B cells. This meta-analysis aims to determine the relationship, if any, between interleukin-7 and COVID-19 severity. Methods: This study was planned as a systematic review and meta-analysis and followed the PRISMA guidelines. Four main electronic databases (Web of Science, PubMed, Scopus, and the Cochrane Central Register of Controlled Trials) were searched from January 1st, 2020 to September 2nd, 2022, to find papers investigating the prognostic significance of interleukin-7 in COVID-19-hospitalized adults. Google Scholar was used in addition to the online database search. A random effects model was used to calculate mean differences and 95% confidence interval (CIs) as well as the I2 statistics for heterogeneity analysis. Results: Seven papers were chosen for meta-analysis findings synthesis. All six trials reported interleukin-7 levels among severe and non-severe COVID-19 patients. Pooled analysis showed that IL-7 levels in the severe group were 62.79Б}81.03 pg/mL, compared to 33.39Б}56.54 pg/mL for the nonsevere group (SMD = -0.17; 95%CI: -0.93 to 0.60; p=0.67). Discussion: Available evidence suggests that elevated levels of IL-7 were not associated with the disease severity of COVID-19. While IL-7 levels alone may not have a substantial impact on COVID-19 severity, the interaction between IL-7 and other cytokines, immune cells, and variables such as viral load and genetics should be investigated further.